1999
DOI: 10.1093/qjmed/92.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Age does not influence levels of HbA1c in normal subject

Abstract: To resolve whether haemoglobin A1c(HbA1c) levels in normal subjects increase with age, we measured HbA1c in 399 patients undergoing routine oral glucose tolerance test (OGTT). The OGTT results categorized the patients into 127 normal, 94 impaired glucose tolerance (IGT) and 178 diabetic. None of these groups showed a significant correlation between HbA1c and age and we cannot, therefore, see a need for age-specific reference ranges for HbA1c. Some of the confusion in the literature may have arisen from less ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 10 publications
4
17
1
1
Order By: Relevance
“…In addition, hemoglobin variants or adducts can cause method-specific interferences. Investigators have also reported a certain degree of between-individual variability in HbA1c resulting from a number of potential factors such as age or race [5456], although the issue of whether these differences are caused by direct HbA1c interference or actual differences in mean glycemia is a subject of debate.…”
Section: Limitations Of Hba1c Testingmentioning
confidence: 99%
“…In addition, hemoglobin variants or adducts can cause method-specific interferences. Investigators have also reported a certain degree of between-individual variability in HbA1c resulting from a number of potential factors such as age or race [5456], although the issue of whether these differences are caused by direct HbA1c interference or actual differences in mean glycemia is a subject of debate.…”
Section: Limitations Of Hba1c Testingmentioning
confidence: 99%
“…Different opinions exist, however, on whether IR increases with age as does IGT [3,4]. Similarly, a positive correlation of fasting plasma glucose (FPG) with age has been reported from some studies [5,6] but not in others [7,8]. The ageing of populations may further increase the burden of type 2 diabetes and pre-diabetes [impaired fasting glucose (IFG)/IGT] on health care systems worldwide [9].…”
Section: Introductionmentioning
confidence: 99%
“…An additional limitation was assigning patients in each of the analyzed groups a constant HbA 1C level throughout the 26-year analysis horizon. However, the clinical study23 by Wiener and Roberts showed that there was no correlation between patient age and HbA 1C levels. The reliability of the methods used in this analysis further strengthen the conclusion that use of the CONTOUR ® TS system to replace manually coded blood glucose meters in diabetes management schemes is associated with a significant advantage with respect to cost utility and cost effectiveness from the perspectives of the payer and the public payer over a 26-year analysis horizon.…”
Section: Discussionmentioning
confidence: 96%